Zmiany stężenia azotu amonowego i azotanowego podczas uzdatniania wody w zakładzie uzdatniania wody Goczałkowice = Concentration changes of ammonium nitrogen and nitrate nitrogen in water treatment processes in wtp Goczałkowice - Nowacka, Anna; Włodarczyk-Makuła, Maria; Macherzyński, Bartłomiej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Water Treatment Plant (WTP) in Goczałkowice belongs to the Upper Silesian Waterworks in Katowice. Production of WTP Goczałkowice is around 45% of the total production of drinking water in the whole waterworks. The paper presents results of studies on changes in the concentration of ammonium nitrogen (N-NH4 +) and nitrate nitrogen (N-NO3-) in water collected after various treatment processes.
Keywords: woda uzdatniona; Goczałkowice; azot amonowy; azot azotanowy; treated water; ammonium nitrogen; nitrate nitrogen